Keberlanjutan Kelestarian Lingkungan: Peran Kunci Lokus Kendali Internal dan Wawasan Lingkungan Dalam Mendorong Perilaku Pro-Lingkungan - Reny Nuraini; Didit Darmawan; Rahayu Mardikaningsih; Mila Hariani; Siti Nur Halizah (TIN: Terapan Informatika Nusantara, 2022)
This study aims to identify how certain factors, such as internal environmental locus of control and environmental insight, can influence pro-environmental behavior. The research method used involved collecting data through questionnaires distributed via Google form to 100 students from tertiary institutions in the city of Surabaya. The sample in this study was selected through an accidental sampling technique, which means that the respondents were selected by accident according to their availability. The data obtained from the questionnaire will be analyzed using multiple linear regression techniques. Multiple linear regression is used to identify the relationship between several independent variables (in this case, internal environmental locus of control and environmental insight) to the dependent variable (pro-environmental behavior). The results of multiple linear regression analysis can provide information about the significant influence of the internal environmental locus of control and environmental insight on pro-environmental behavior